Oxytocin Receptor Single-Nucleotide Polymorphisms Are Related to Maternal-Infant Co-Occupation and Infant Sensory Processing - Nicki L. Aubuchon-Endsley; Madeline Hudson; Brittany Banh; Emma Opoku; Jason Gibbs; Bryan M. Gee (MDPI AG, 2024)
Background: Caregiver-infant reciprocity is related to infant/toddler development and health. However, there is a dearth of research on reciprocity variables like co-occupation and developmental variables such as infant/toddler sensory processing/preferences, and it is important to understand the biopsychosocial mediators of these relations. These include novel genetic markers like maternal oxytocin receptor single-nucleotide polymorphisms (OXTR SNPs). Therefore, this study examined whether mothers carrying risk alleles for three OXTR SNPs displayed different co-occupational behaviors with their infants and whether their infants/toddlers showed different sensory processing/preferences. Methods: Data from the Infant Development and Healthy Outcomes in Mothers Study included prenatal saliva samples assayed for OXTR SNPs, 6-month postnatal behavioral observations coded for maternal-infant co-occupations (reciprocal emotionality, physicality, and intentionality), and 10-, 14-, and 18-month postnatal, maternal-reported Infant/Toddler Sensory Profiles (classified as within or outside the majority range for low registration, sensory seeking, sensory sensitivity, and sensory avoiding). Results: Mothers with rs53576 risk allele A engaged in more frequent reciprocal emotionality, while those with rs2254298 risk allele A engaged in less frequent reciprocal emotionality but more frequent reciprocal intentionality. Mothers with rs53576 risk allele A had infants with 11 times greater odds of being outside of the majority range for sensation avoiding at 10 months old. Conclusions: The results converge with the literature supporting links between OXTR SNPs, caregiver reciprocity, and infant/toddler development but extend the findings to relatively novel constructs (caregiver-infant co-occupations and infant/toddler sensory processing/preferences).